Synthesis Of Diimine nickel (II) complex and its catalysis study in sonogashira reaction - Kuan, Suzie Hui Chin (Universiti Malaysia Sarawak, UNIMAS, 2013)
The cross-coupling reaction catalyzed by various transition metal complexes is the most powerful synthetic tools for the generation of carbon–carbon bonds. Therefore, significant efforts have been put on the modification of ligands to increase the catalytic activity of the complex. In this project, two diimine compounds were synthesized by condensation reaction in ethanol at room temperature and used to form complexes with NiCl2 .6H2O. The synthesized diimine compounds and their complexes were characterized using UV-visible spectroscopy, FTIR, NMR spectroscopy and GCMS data. Besides, the [NiII(L)]Cl2 complexes are utilized as a catalyst in the Sonogashira cross coupling reaction between 4-bromoanisole and 2-methylbut-3-yn-2-ol in order to examine its catalytic efficiency. Results shown that the [NiII(L)]Cl2 complexes are incapable of inducing the formation of cross coupling reaction due to the formation of homo-coupled product that is 2,7-dimethyl-octa-3,5 diyne-2,7- diol.